2023
DOI: 10.2196/47065
|View full text |Cite
|
Sign up to set email alerts
|

The Perception of Health Care Practitioners Regarding Telemedicine During COVID-19 in Saudi Arabia: Mixed Methods Study

Heba Alqurashi,
Rafiuddin Mohammed,
Amany Shlyan AlGhanmi
et al.

Abstract: Background Telemedicine is a rapidly evolving field that uses information and communication technology to provide remote health care services, such as diagnosis, treatment, consultation, patient monitoring, and medication delivery. With advancements in technology, telemedicine has become increasingly popular during the COVID-19 lockdown and has expanded beyond remote consultations via telephone or video to include comprehensive and reliable services. The integration of telemedicine platforms can en… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 33 publications
1
2
0
Order By: Relevance
“…Several national and international studies highlight the positive impact of increasing healthcare professionals’ awareness of the effective utilization and integration of TM in healthcare. 52 , 60–63 This was in agreement with the results of our study, where a significant difference was shown between the TM users group and the non-user group in the awareness parameter in favor of the TM user group. This increased healthcare providers’ awareness about the effective use of TM increases the acceptability of it among the patients and the healthcare providers, 36 , 63–65 facilitates and accelerates the integration of the TM within the PHCs.…”
Section: Discussionsupporting
confidence: 92%
“…Several national and international studies highlight the positive impact of increasing healthcare professionals’ awareness of the effective utilization and integration of TM in healthcare. 52 , 60–63 This was in agreement with the results of our study, where a significant difference was shown between the TM users group and the non-user group in the awareness parameter in favor of the TM user group. This increased healthcare providers’ awareness about the effective use of TM increases the acceptability of it among the patients and the healthcare providers, 36 , 63–65 facilitates and accelerates the integration of the TM within the PHCs.…”
Section: Discussionsupporting
confidence: 92%
“…A total of twelve articles were included in the review for having met the inclusion considerations Albarrak et al, 2021;Alghamdi et al, 2022;Aloyuni et al, 2020;Alqurashi et al, 2023;Bashir & Bastola, 2018;Bashir et al, 2023;Moussa et al, 2023;Ullah et al, 2021;Idriss et al, 2022;. The articles conformed to two methodologies -one mixed research and the rest applied the quantitative design.…”
Section: Resultsmentioning
confidence: 99%
“…Other also expressed a feeling that technological limitations, willingness among staff, location of the systems and diagnostic reliability hinder the effective use of telemedicine (Aloyuni et al, 2020). Nevertheless, some studies also identified recommendations for better adoption and use among the healthcare staff, including continuous training the healthcare workers, continuous evaluation of the system, consideration of organizational culture and systems (Alqurashi et al, 2023).…”
Section: Barriers and Other Factors Affecting Healthcare Workers' Per...mentioning
confidence: 99%